2016
DOI: 10.1080/17470218.2015.1034143
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between psychometric schizotypy, scan path length, fixations on the eyes and face recognition

Abstract: Psychometric schizotypy in the general population correlates negatively with face recognition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 89 publications
0
9
1
3
Order By: Relevance
“…Experiment 2 replicated the correlation between correct face identifications and anxiety in female participants. These results suggest that associations between personality and face perception are limited and are confined to anxiety and facets of neuroticism (also see Hills, Eaton, & Pake, 2016 ; Megreya & Bindemann, 2013 , who found no link between face recognition and extraversion but see other work detailed below). Socially anxious individuals may avoid social interactions (see Bögels et al, 2010 ), leading to less exposure to faces, accounting for the specific reduction in face recognition ability.…”
Section: Introductionmentioning
confidence: 84%
“…Experiment 2 replicated the correlation between correct face identifications and anxiety in female participants. These results suggest that associations between personality and face perception are limited and are confined to anxiety and facets of neuroticism (also see Hills, Eaton, & Pake, 2016 ; Megreya & Bindemann, 2013 , who found no link between face recognition and extraversion but see other work detailed below). Socially anxious individuals may avoid social interactions (see Bögels et al, 2010 ), leading to less exposure to faces, accounting for the specific reduction in face recognition ability.…”
Section: Introductionmentioning
confidence: 84%
“…Nonetheless, it is also possible that higher levels of empathy prompt perceivers to allocate more attention to faces. Another study by Hills et al (2016) reported that psychometric schizotypy, a cluster of traits related to difficulties in social situations (e.g., anxiety), is negatively related to face recognition accuracy. Three studies have also shown a direct link between general anxiety and face recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Тем не менее в данной работе у лиц с шизотипическим расстройством в ранее проведенных исследованиях было обнаружено уменьшение траектории прослеживания вплоть до застывания. Ранее также было установлено, что меньшая длина траектории просмотра связана с менее эффективным выполнением заданий по распознаванию лиц [11] или обнаружению преследования [17]. Следовательно, у больных с шизотипическим расстройством квазисимультанная стратегия восприятия оказывается неэффективной.…”
Section: Discussionunclassified
“…Высокая частота коротких непроизвольных саккад отражает повышенную отвлекаемость таких больных на несущественную информацию и свидетельствует об ослабленном тормозном механизме в системе фиксации и процессах визуального восприятия [10,11]. Неоднократно отмечалась недостаточная избирательность больных шизофренией или шизотипическим расстройством, при которой нерелевантные стимулы обрабатываются ими в той же степени интенсивно, как и релевантные [11].…”
unclassified
See 1 more Smart Citation